Reference intervals for serum immunoglobulin A levels in Brazilian children aged 1 to 10 years: a population-based study - Sandra Breder Assis; Natasha Slhessarenko; Cor Jesus Fernandes Fontes (Elsevier, 2023)
Objective: To determine reference intervals (RI) for serum immunoglobulin A (IgA) levels in healthy children aged 1 to 1 0 years residing in the central region of Brazil. Methods: This cross-sectional study was conducted on 1,743 healthy children randomly selected from kindergartens and public schools in Cuiabá, MT, Brazil. The IgA RIs were defined using the statistical methods postulated by the guidelines of the United States Clinical and Laboratory Standards Institute, the nonparametric bootstrap method, and Horn's robust method after the correction of discrepancies by Tukey's, Dixon's, and Horn's methods, respectively. The results were defined based on the values contained between the 2.5th and 97.5th percentiles and their respective 95% confidence intervals. Results: Partition by sex was not necessary to determine the IgA RI of the studied children. Homogeneous subgroups were identified among children aged 1-<2, 2-<5, and 5-<11 years, whose IgA-specific RIs were determined. Conclusion: The serum IgA RIs were established for three groups of Brazilian children aged 1-11 years, which differed from those currently applied in Brazilian pediatric practice and from those defined by international studies. This definition will help Brazilian pediatricians formulate an accurate diagnosis and facilitate decision-making.